Artesunate Inhibits Neointimal Hyperplasia by Promoting IRF4 Associated Macrophage Polarization - Jinlin Miao; Yule Yong; Zhaohui Zheng; Kui Zhang; Wei Li; Jiayi Liu; Siyi Zhou; Juan‐juan Qin; Haoyang Sun; Yatao Wang; Xianghui Fu; Xing Luo; et al. (Advanced Science)
Abstract Vascular restenosis is a serious clinical issue initiated and aggravated by macrophage inflammation, with no effective treatments available, in cardiovascular and autoimmune diseases. However, the untapped mechanisms and new targets that can regulate macrophage polarization and vascular restenosis remain elusive. The research identifies interferon regulatory factor 4 (IRF4) expression as crucial in macrophage polarization during arterial restenosis. Myeloid‐specific Irf4 deficiency and overexpression experiments showed that IRF4 promoted M2 macrophage polarization, inhibited M1 macrophage transitions, and disrupted the interaction between macrophages and vascular smooth muscle cells to reduce neointimal hyperplasia by directly upregulating krüppel like factor 4 (KLF4) expression. Artesunate, an FDA‐approved drug, is screened as a potent activator of IRF4 expression in M2 polarization, and its treatment attenuated arterial restenosis in rodents and non‐human primates. The findings reveal a significant protective role of IRF4 in the development of neointimal hyperplasia by regulating macrophage polarization, and artesunate may be proposed as a novel therapy for vascular restenosis.